Resistance to the Phosphaturic and Calcemic Actions of Parathyroid Hormone during Phosphate Depletion: PREVENTION BY 1,25-DIHYDROXYVITAMIN D(3) - Gloor, H. J. (1979)
Recent observations indicate that in thyroparathyroidectomized (TPTX) rats fed a low (0.2 g/100 g) phosphorus diet, the tubular phosphaturic response to parathyroid hormone (PTH) remains markedly blunted even when it is assessed at normal or high plasma concentration and filtered load of inorganic phosphate (Pi). Because 1,25-dihydroxyvitamin D(3) [1,25(OH)(2)D(3)] decreases the tubular capacity to reabsorb Pi when chronically administered to TPTX rats, we have studied whether this vitamin D(3) metabolite could specifically increase the phosphaturic response to PTH in phosphate-deprived animals. The results show that in Vitamin D-replete TPTX rats fed a low (0.2 g/100 g) phosphorus diet, 1,25(OH)(2)D(3) (2 × 13 pmol/d i.p. for 7 d) markedly enhanced the acute tubular phosphaturic response to PTH (2.5 IU/h i.v.) without affecting the action of the peptide hormone on Ca reabsorption and cyclic-3′,5′-AMP excretion. The influence of 1,25(OH)(2)D(3) on the phosphaturic response to PTH could not be ascribed to an increased plasma concentration and(or) filtered load of Pi during the administration of the peptide hormone. However, it could be, at least in part, related to the elevation in the basal level of plasma Pi which was observed in the 1,25(OH)(2)D(3)-treated animals. The results also indicate that 1,25(OH)(2)D(3) significantly enhanced the calcemic response to PTH, which was blunted in these conditions of phosphate deprivation. Unlike 1,25-(OH)(2)D(3), 25-hydroxyvitamin D(3) did not unmask the phosphaturic effect of PTH in phosphate-depleted animals, even when given in doses 100 times larger. Thus, 1,25(OH)(2)D(3) displays a selective and powerful activity in preventing the occurrence of tubular resistance to the phosphaturic action of PTH during Pi depletion. This finding suggests the existence of an important interaction between dietary Pi, 1,25(OH)(2)D(3), and PTH in the homeostasis of phosphate.